Asupan Magnesium dan Kadar Magnesium Serum dengan Tekanan Darah Pasien Rawat Jalan Penderita Hipertensi - Rahmawati, Aprilia Kusuma; Krisnamurni, Sri; Jaelani, Mohamad (JURNAL RISET GIZI, 2013)
Background : Hypertension is the third major cause of death in Indonesia. The prevalence of hypertension 37% in Central Java was higher the national average   (Riskesdas 2007).  5395 hypertensive patients visited “Puskesmas” I Mranggen in 2012. One of the factors affect hypertension is low magnesium intake, which was correlated with serum magnesium levels. Hipomagnesemia more common in hypertensive subjects, can  increased vascular tone and affect the activity of vasoconstrictor and dilator responses to a variety of agents that cause an increase in peripheral resistance then increases blood pressure.Objective : This study was designed to determine the relationship between magnesium intake and serum magnesium levels with a blood pressure of hypertensive subjects At On The Way Care Unit In “Puskesmas” Mranggen I, DemakMethod : The present study was a cross sectional study. Thirty three (13 males and 20 females) hypertensive outpatients subjects were recruited into the study. Data collected included blood pressure was measured using a sphygmomanometer samples, serum magnesium levels were measured by the method using Photometric test xylidyl blue. Data of magnesium intake were obtained using a semi-quantitative food frequency. Data were analyzed using Rank Spearman test with α = 0.05.Results : The percentage of subjects younger than 45 years was 15,2% males and 18,2% in females. And older than 45 years was 24,2% in males and 42,4% females. No associations was found between magnesium intake with systolic blood pressure (p = 0.0203) and diastolic (p = 0.252). Magnesium intake was found to be associated with serum magnesium levels (p=0,014 to r=0,423), and also between  serum magnesium levels with systolic blood pressure of (p = 0.012;  r = -0.433) and diastolic (p = 0.025    r = -0.390) hypertension subjects at On The Way Care Unit In “Puskesmas” Mranggen I, Demak.Conclusions : There is a correlations between magnesium intake and serum magnesium levels, and serum magnesium levels with systolic blood pressure. Further studies are needed in hypertension to determine whether magnesium intake was needed in dietetics therapy for hypertensive subjects.